2002
DOI: 10.1128/aem.68.1.82-85.2002
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Beauvericin and Enniatins in Wheat Affected by Fusarium avenaceum Head Blight

Abstract: We evaluated Fusarium contamination and the levels of hexadepsipeptide mycotoxins in 13 wheat samples affected by head blight in Finland. Fusarium avenaceum was the dominant species (91%) isolated from all samples, but isolates of F. culmorum (4%), F. tricinctum (3%), and F. poae (2%) also were recovered. Beauvericin (0.64 to 3.5 g/g) was detected in all 13 samples. Enniatin B (trace to 4.8 g/g) was detected in 12 samples, enniatin B 1 (trace to 1.9 g/g) was detected in 8 samples, and enniatin A 1 (trace to 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(117 citation statements)
references
References 15 publications
6
104
2
5
Order By: Relevance
“…The Finnish raw cereal samples contained also very low concentrations of BEA [15]. However, higher concentrations have been reported in Finnish grains [16].…”
Section: Resultsmentioning
confidence: 96%
“…The Finnish raw cereal samples contained also very low concentrations of BEA [15]. However, higher concentrations have been reported in Finnish grains [16].…”
Section: Resultsmentioning
confidence: 96%
“…ENNs and BEA, two secondary metabolites of the genus Fusarium, are worldwide contaminants of grain-based foodstuff [29]. Especially in Norwegian and Finnish grain samples, a high prevalence of ENNs and BEA was shown with a maximum concentration of 18 300 ppb for ENN B in the year 2001 [30].…”
Section: Discussionmentioning
confidence: 96%
“…[10][11][12] While beauvericin is produced as the sole cyclohexadepsipeptide metabolite by the former entomopathogenic fungi, it is often co-produced as a minor constituent with the structurally related enniatins by Fusarium species. [13][14][15][16] Recently we reported that Isaria tenuipes, a specific pathogen of Lepidoptera pupa or larva, and several phylogenetically closely related species constantly produce beauvericin when fermented in potato dextrose broth (PDB). 17 Isaria tenuipes has been used as folk medicines or health food, for good health, in East Asian countries, Japan, China, and South Korea.…”
Section: Introductionmentioning
confidence: 99%